ประวัติศาสตร์นิพนธ์ด้านสถาปัตยกรรมสมัยใหม่ในประเทศไทย/ The Historiography of Modern Architecture in Thailand - Fusinpaipoon, Chomchon (NAJUA: History of Architecture and Thai Architecture, 2016)
บทคัดย่อ บทความนี้นำเสนอพัฒนาการของประวัติศาสตร์นิพนธ์ด้านสถาปัตยกรรมสมัยใหม่ในประเทศไทย ในแง่ของกรอบทฤษฎีในการศึกษา หลักฐานที่ใช้ กรอบเวลาในการศึกษา และปัจจัยแวดล้อมทางสังคมวัฒนธรรมและการเมืองที่ส่งผลต่อประวัติศาสตร์นิพนธ์ด้านนี้ เนื้อหาเริ่มด้วยการอภิปรายถึงจุดกำเนิดของงานวิจัยที่สามารถเรียกได้ว่าเป็นประวัติศาสตร์นิพนธ์ด้านสถาปัตยกรรมสมัยใหม่ในประเทศไทย ซึ่งเกิดขึ้นในช่วงทศวรรษที่ 2530 ในช่วงที่การเจริญเติบโตทางเศรษฐกิจของประเทศไทยและกิจกรรมเกี่ยวกับการก่อสร้างขยายตัวอย่างมาก ควบคู่ไปกับกระแสการตั้งคำถามเกี่ยวกับอัตลักษณ์ของชาติในภาวะที่ดูเหมือนว่าโลกาภิวัตน์กำลังทำให้เมืองทุกแห่งในโลกมีลักษณะเหมือนกันเข้าไปทุกขณะ จากนั้นได้อภิปรายถึงงานวิจัยในช่วงสิบปีให้หลัง ซึ่งมีการใช้กรอบทฤษฎีในการศึกษา หลักฐานที่ใช้ และการกำหนดกรอบเวลาในการศึกษาที่หลากหลายและเริ่มตั้งคำถามถึงความสัมพันธ์ระหว่างสถาปัตยกรรมสมัยใหม่และสภาวะของความเป็นสมัยใหม่ในประเทศไทยชัดเจนขึ้น Abstract This paper provides a survey of how the historiography of modern architecture in Thailand has been developed in terms of the oretical frameworks, evidence, time frames, and socio-political factors that have contributed to the development. It discusses the unique circumstances, namely the economic boom and a concern about national identity in architecture that ignited the sense of a need for what might be considered a history of modern architecture in Thailand during the 1980s and 1990s. Following that, this paper provides a review of recent scholarship on the relationship between architecture and modernity in Thailand to show the current stage of critical research on the topic. It also discusses how postcolonial theories, previously unpopular and seldom explicitly used in Thai studies because Thailand was not colonised by any western power, might benefit the research about modern architecture in the country.